(untitled) (Global Journal of Science Frontier Research, 2017)
A total of 48 individuals of the Chinese mitten crab (Eriocheir sinensis) were used to study the association between micro-satellite DNA markers and their resistance to the trembling disease. The crabs used in this study were collected from an aquatic breeding farm in Yandu District, Yancheng city, Jiangsu Province in China. Twenty four of the crabs were collected from a pond heavily infested with trembling disease and these manifested clear signs of the disease while the remaining 24 crabs were collected from a pond free of the disease and these were all healthy. The Shannon Diversity Index was used to analyze the association of the individual marker alleles with resistance to the trembling disease. The results showed that the mean number of alleles (Na), the mean number of effective alleles (Ne), mean observed heterozygosity (Ho), mean expected heterozygosity (He), mean polymorphic information content (PIC) and mean Shannon index (I)in the individual populations were 4.2, 3.2, 0.6628, 0.6466,0.6221 and 1.2, respectively.